Family composition and distribution of fish larvae in La Restinga Lagoon, Margarita Island, Northeastern Venezuela - Montserrat, Esteve; Brito, Ana; Trujillo, Edgar (Ciencia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; @font-face font-family:Bookman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Bookman Old Style"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This work is a contribution to the knowledge of the species composition, the abundance and the spatiotemporal distribution of fish larvae in the coastal lagoon La Restinga, Margarita Island, Northeastern Venezuela. Samples were collected from June to September 1996, in four lagoon interior stations, and from January to June 1998, at the lagoon mouth. In the lagoon interior 1223 larvae belonging to 18 families, 30 genera and 24 species, were collected. The most frequent families were: Gobiidae, Engraulidae, Sparidae and Carangidae, which embraced 83.07% of the collected larvae. Two abundance peaks occurred, one in mid-July and the other in mid-August. At the lagoon mouth 5575 larvae representative of 13 families, 12 genera and 12 species, were collected. The most frequent families were: Gobiidae, Engraulidae, Blenniidae and Grammistidae, comprising over 95.00% of the collected larvae. Two abundance peaks occurred, one in early March and the other in late May. Through both sampling periods representatives of 21 families, 36 genera and 33 species were collected, indicating that La Restinga is a spawning and nursery ground for resident fish species while no resident species rely on the area for survival of the early stages.